Predators and Profits: 100+ Ways for Investors to Protect Their Nest Eggs - Howell, Martin (Pearson, 2003)
Predators and Profits helps you uncover the kind of scandals that brought down Enron and Worldcom. Are problem stocks still lurking in your portfolio? Learn how to identify them, while there's still time. Leading Reuters business journalist Martin Howell identifies more than 100 crucial red flags: hidden risks from greedy executives, sleepy boards, accounting shenanigans, and questionable corporate culture. It's all public information: Martin Howell shows how to find it, assess it, and act on it.